2019
DOI: 10.1093/icvts/ivz095
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic or aneurysmal aberrant subclavian arteries: results of surgical and hybrid repair

Abstract: OBJECTIVES Indications and techniques of repair for symptomatic or aneurysmal aberrant subclavian arteries (ASA) are controversial. This study analyses presentation, treatment and outcome of patients with symptomatic and/or aneurysmal ASA. METHODS Retrospective analysis of consecutive adult patients undergoing symptomatic and/or aneurysmal ASA repair between January 2000 and June 2016. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 19 publications
0
4
1
Order By: Relevance
“…Our study has several clinical implications. First, unlike previous studies in which dysphagia was the most common symptom at the time of diagnosis, our symptomatic patients reported shortness of breath to be the most prevalent one 22–24 . This finding suggests that the absence of dysphagia should not rule out an ARSA.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Our study has several clinical implications. First, unlike previous studies in which dysphagia was the most common symptom at the time of diagnosis, our symptomatic patients reported shortness of breath to be the most prevalent one 22–24 . This finding suggests that the absence of dysphagia should not rule out an ARSA.…”
Section: Discussioncontrasting
confidence: 91%
“…First, unlike previous studies in which dysphagia was the most common symptom at the time of diagnosis, our symptomatic patients reported shortness of breath to be the most prevalent one. [22][23][24] This finding suggests that the absence of dysphagia should not rule out an ARSA. Second, we found that ARSA patients taller than 158 cm (62 in) had greater odds of symptoms.…”
Section: Discussionmentioning
confidence: 97%
“… 15 , 16 KD develops as an aneurysmal enlargement of the descending aorta at the aberrant vessel origin, with a 19% to 53% risk of dissection or rupture. 17 , 18 , 19 Our patient did not have concomitant KD, although the origin of her ARSCA was ectatic. The presence of a KD would not have altered our operative approach, because the TBE device would have excluded its origin.…”
Section: Discussionmentioning
confidence: 65%
“…The 4 postoperative strokes that occurred in this series (9.3%) were related to embolic events, 3 of which occurred after complex repair. In the literature, postoperative stroke rates varied between 2.6 and 16% and were likely related to aortic arch and SAT manipulations and/or to endovascular wires and device-related injuries [ 21–23 ]. Other studies do not report a postoperative stroke after ASCA hybrid repair [ 14 , 16 ].…”
Section: Discussionmentioning
confidence: 99%